P435Extracellular vesicles mediate cardioprotection exerted by remote ischemic preconditioning in rats. (15th July 2014) - Baranyai, T; Giricz, Z; Varga, ZV; Sipos, P; Paloczi, K; Kittel, A; Buzas, E; Ferdinandy, P
Abstract: Background: Remote ischemic preconditioning (RIPC) of the heart (i.e. brief ischemia/reperfusion cycles, subjected to a remote organ or a remote area, reduce the consecutive damage of a sustained cardiac ischemia. Although, its mechanism has been investigated thoroughly, exact interorgan transfer mechanisms of cardioprotection by RIPC are required to be further investigated. Exosomes and microvesicles/microparticles are vesicles of 30-100 nm and 100-1000 nm in diameter, respectively (collectively termed extracellular vesicles [EVs]). As EVs are able to shuttle proteins, mRNAs and microRNAs, they are ideal candidates for inter-organ communication. However, whether EVs are involved in RIPC, is unknown. Purpose: Here we investigated whether (1) IPC induces release of EVs from the heart, and (2) EVs are necessary for cardioprotection by RIPC. Methods: Hearts of male Wistar rats were isolated and perfused as described by Langendorff. Hearts were exposed to 3 × 5 min global ischemia/reperfusion cycles (IPC) or 30 min aerobic perfusion, while coronary perfusates were collected. Coronary perfusates of these donor hearts were given to another set of recipient isolated hearts either unharmed or depleted of EVs by differential ultracentrifugation. Infarct size was determined by triphenyl tetrazolium chloride at the end of 30 min global ischemia and 120 min reperfusion period. The presence or absence of EVs in perfusates was confirmed by dynamic light scattering, the EV marker hsp60 Western blot, and electron microscopy. Results: IPC markedly increased EV release from the heart as assessed by HSP60 immunoblot. Administration of coronary perfusate from IPC donor hearts attenuated infarct size in non-preconditioned recipient hearts (12.9 ± 1.6% vs. 25.0 ± 2.7%, respectively), similarly to cardioprotection afforded by IPC (7.3 ± 2.7% vs. 22.1 ± 2.9%, respectively) on the donor hearts. Furthermore, perfusates of IPC hearts depleted of EVs failed to exert cardioprotection in recipient hearts (22.0 ± 2.3%). Conclusions: This is the first demonstration that EVs released from the heart after IPC are necessary for cardioprotection by RIPC, evidencing the importance of vesicular transfer mechanisms in remote cardioprotection.